2016
DOI: 10.1111/aec.12478
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and conservation of insectivorous bats in fragmented areas of macadamia production in eastern Australia

Abstract: Microbats perform important ecological services in agro-ecosystems, but several species are globally threatened by loss of roosting and breeding habitats. The successful conservation of bats in agricultural land requires adequate knowledge of their ecology. Using ultrasonic recorders, we studied the activity of insectivorous bats in areas of macadamia production in eastern Australia at two spatial scales: across woodland-orchard transects at the local scale and across three levels of fragmentation at the lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…The distance to water, the altitude above sea level and the height of bat houses did not significantly influence bat house occupancy in our study. While water availability is known to influence bat activity (Crisol-Martínez et al, 2016; Grindal, Morissette & Brigham, 1999; Rainho & Palmeirim, 2011) the bat houses in this study were erected within a range of two to 680 m from the closest water source, all within the known home range of even small plain-faced bats (Monadjem et al, 2010b). We suggest that the distance to water might be more significant in arid regions compared to our high rainfall subtropical study area.…”
Section: Discussionmentioning
confidence: 99%
“…The distance to water, the altitude above sea level and the height of bat houses did not significantly influence bat house occupancy in our study. While water availability is known to influence bat activity (Crisol-Martínez et al, 2016; Grindal, Morissette & Brigham, 1999; Rainho & Palmeirim, 2011) the bat houses in this study were erected within a range of two to 680 m from the closest water source, all within the known home range of even small plain-faced bats (Monadjem et al, 2010b). We suggest that the distance to water might be more significant in arid regions compared to our high rainfall subtropical study area.…”
Section: Discussionmentioning
confidence: 99%
“…The distance to water, the altitude above sea level and the height of bat houses did not significantly influence bat house occupancy in our study. While water availability is known to influence bat activity (Crisol-Martínez et al, 2016;Grindal et al, 1999;Rainho & Palmeirim, 2011) the bat houses in this study were erected within a range of two to 680 meters from the closest water source, all within the known home range of even small plain-faced bats (Monadjem et al, 2010b). We suggest that the distance to water might be more significant in arid regions compared to our high rainfall subtropical study area.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 10 min point counts found 47 out of the 62 species recorded with acoustic recorders, which indicates that acoustic recorders can be more efficient as they require a lower survey effort and detect birds that may be hidden by branches or foliage in the structurally complex macadamia orchards [24,25]. Besides birds and arthropods, the mixed forest-orchard landscapes in Bundaberg maintain rich insectivorous bat communities, which are also highly active in macadamia stands [29]. A study of macadamia in South Africa has also indicated the importance of macadamia landscapes as habitat for birds, as well as bats and monkeys [48].…”
Section: The Importance Of Macadamia Landscapes As Habitat For Birds mentioning
confidence: 92%
“…Additionally, during this period the macadamia phenology was between the peak of flowering and early nut development phases. At this time, the numbers of insect herbivores normally increase on the crop [29], so insecticide treatments are generally conducted in the orchards.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation